Enhancing School Resource Officers Effectiveness through Online Professional and Job Embedded Coaching, Miami-Dade County, Florida, 2018-2020 - Espelage, Dorothy L. ([Verlag nicht ermittelbar], 2021)
This pilot project was aimed at promoting the skills of School Resource Officers, through an innovative online professional development platform. Conducted in partnership with Florida Public Schools, this project involved the development, testing, and refinement of online modules around trauma-informed care, social emotional learning, restorative problem-solving, and cultural competence. After development of the four modules, a small pilot evaluation was conducted with K-12 School Security Professionals to assess for efficacy and scalability. The survey assessed knowledge retention, and gathered demographic information including: age, gender, race/ethnicity, and education level.